Tourism, Employment Generation and Foreign Exchange Earnings in Nepal - Bhattarai, Kumar; Upadhyaya, Ghanshyam; Bohara, Surendra Kumar (Journal of Tourism and Hospitality Education, 2021)
An activity of travelling has remained one of the leading contributors of global economic activities, particularly, in employment generation and foreign exchange earnings. With the 56-folds growth of international tourist arrivals from 1950 to 2018 globally, Nepalese tourism industry is widening its scope for employment generation and foreign exchange earnings. The aim of this study is to analyze role of tourism on employment generation and foreign exchange earnings in Nepal. For this, a descriptive study design was employed. Analysis was done by using secondary data of the period 2010-2019. Number of tourist arrival in 2019 (1,197,191) was found nearby double compared to the 2010 (602,867), however, the status of average length of stay remained almost same within this period. Data show, on average, that most of the tourists had visited Nepal for holiday celebration (58.6%), followed by trekking and mountaineering (11.2%) and pilgrimage (11.4%). Average annual share of tourism earnings on total export earnings in 2010-2018 was 21.7% whereas share of tourism earnings on total foreign exchange earnings was 6.2%. It is estimated that every 6 tourists visited create 1 employment opportunity in Nepal. Despite the situation of almost double in number of tourist arrival from 2010 to 2019, this study concludes that there was no significant increase in the share of tourism in total foreign exchange earnings and total employment in Nepal.